1997
DOI: 10.1590/s0074-02761997000300008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Trypanosoma cruzi Strains Isolated from Chronic Chagasic Patients, Triatomines and Opossums Naturally Infected from the State of Rio Grande do Sul, Brazil

Abstract: Thirty-five

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
3
19
0
5
Order By: Relevance
“…However, TcII is the most important agent of severe heart disease, including megacardia, and digestive syndromes, such as megaesophagus and megacolon, mainly in central and eastern regions of Brazil [6][7][8]19,20 . The TcVI genotype is prevalent in Southern Brazil (Rio Grande do Sul), and it has been also associated with cardiac and digestive forms 7,8,24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, TcII is the most important agent of severe heart disease, including megacardia, and digestive syndromes, such as megaesophagus and megacolon, mainly in central and eastern regions of Brazil [6][7][8]19,20 . The TcVI genotype is prevalent in Southern Brazil (Rio Grande do Sul), and it has been also associated with cardiac and digestive forms 7,8,24 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] These reservoirs include marsupials, edentates, and rodents. 7,9,10 The proportion of infected reservoirs is variable according to the local epidemiologic situation, and its magnitude depends on the density and rates of infected triatomine vectors in each ecologic niche.…”
Section: Introductionmentioning
confidence: 99%
“…In Rio Grande do Sul, another state in Southern Brazil, Fernandes et al (1997), analyzing isoenzyme and RAPD profiles of T. cruzi strains isolated from reservoirs, triatomines and humans, two independent groups of strains were also observed, related to the sylvatic transmission cycle and the domestic one. These authors observed a close correlation between the main groups defined by RAPD and by isoenzyme profiles.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%